Treatment Patterns and Clinical Outcomes in Advanced Lung Neuroendocrine Tumors in Real‐World Settings: A Multicenter Retrospective Chart Review Study. (4th January 2019) - Dasari, Arvind; Bergsland, Emily K.; Benson, Al B.; Cai, Beilei; Huynh, Lynn; Totev, Todor; Shea, Jerome; Duh, Mei Sheng; Neary, Maureen P.; Dagohoy, Cecile G.; Shih, Brandon E.; Maurer, Victoria E.; et al.
Abstract: Background: Using data from four tertiary referral centers in the U.S., we assessed real‐world treatment patterns and clinical outcomes of patients with advanced lung neuroendocrine tumors (NETs). Subjects, Materials, and Methods: We performed a retrospective chart review of adult patients with locally advanced/metastatic (typical/atypical) lung NETs treated between July 2011 and December 2014. Index date was histologically confirmed typical/atypical carcinoid tumor diagnosis date. Data included baseline characteristics, treatment patterns, progression, death, and lung NET‐related health care resource use from index date through last contact/death. Time to treatment discontinuation and first progression, time from first to second progression, and overall survival (OS) were estimated using Kaplan‐Meier analysis. Results: We identified 83 patients; 19 (23%) had functional NET. First‐line treatments included somatostatin analogs (SSAs) alone (56%) or in combination with other therapies (6%), cytotoxic chemotherapy (20%), external beam radiation therapy (EBRT) (9%), liver‐directed therapy (LDT) (4%), and everolimus/other (5%). Sixty patients had second‐line therapy including SSA alone (18%) or in combination (40%), cytotoxic chemotherapy (17%), everolimus (12%), LDT (7%), EBRT (3%), and other treatments (3%). Median time (months) to first‐line discontinuation were as follows: SSAs, 43.3; cytotoxic chemotherapy, 3.6. Overall median time (months) to investigator‐assessed progression following treatment initiation was 12.4. Median OS (months) following treatment initiation was 66.4 for all patients and 81.5 for patients receiving SSAs. Conclusion: SSAs, alone and in combination, are common treatments for advanced lung NETs. Patients have additional treatment options and relatively long survival compared with patients with other advanced cancers. Treatment pattern assessment following approval of newer treatments is needed. Abstract : This article assesses long‐term, real‐world treatment patterns and clinical outcomes of patients with lung neuroendocrine tumors (NET) at four tertiary cancer centers in the U.S., considering the FDA‐approved treatment and NCCN recommendations. A retrospective patient chart review was performed to determine treatment patterns and clinical outcomes for patients with advanced lung NETs.